Avaliação da segurança e qualidade do tomate quanto aos agrotóxicos com a tecnologia de ultrassom - Bissacotti, Anelise Pigatto (2023)
The improper use of pesticides to prevent and control diseases and plagues in tomato cultivation results in residues of these substances remaining in the fruit, representing a health risk to the consumer. Ultrasound has proven to be advantageous in food processing and efficient in removing pesticides. Hence, this study sought to evaluate whether tomato consumption contributed to the risk of chronic exposure to pesticide residues and to identify the effects of ultrasound application at different times on these substances present in the fruit and their quality. Was estimated the risk of chronic exposure of the Brazilian population to 46 pesticides quantified in tomato samples by the Programa de Análise de Resíduos de Agrotóxicos em Alimentos (PARA) from 2013 to 2015. It was found that the Brazilian population was not exposed to chronic dietary risk by consuming tomatoes contaminated with the pesticides since the percentage of acceptable daily intake (%ADI) calculated ware less 100%. Studies that tested the efficiency of ultrasound in removing pesticide residues in food were identified and analyzed through a integrative review. Moreover, was verified that ultrasound removes pesticide residues in food, and various factors interfere with the decontamination promoted by this technology. Various percentages of pesticide removal by ultrasound were reported in the studies. Posteriorly, was analyzed the effects at 25 kHz ultrasound on pesticide residues present in ‘Longa Vida’ tomatoes after 0 (control), 5, 10, 15, 20, 25, 30, and 35 min of treatment. Pesticides were extracted, determined, and quantified in the samples using the modified QuEChERS acetate multi-residue method and ultrahigh performance liquid chromatography coupled to mass spectrometry. Eight pesticides were detected: acetamiprid, chlorantraniliprole, clothianidin, ethophenproxy, imidacloprid, thiamethoxam, carbendazim, and thiophanate-methyl, at concentrations below the maximum residue limit (MRL). Samples showed a higher residual concentration of acetamiprid and etofenproxide than the control sample. Most samples (n = 46) showed the absence of trace amounts of carbendazim, while in two, it was present at concentrations below the limit of quantification. Concentrations of chlorantraniliprole, imidacloprid, and thiophanate-methyl were reduced after ultrasonic treatment. The ultrasound did not interfere with clothianidin concentrations. Thiamethoxam was quantified in only two samples after the treatments. Finally, quality attributes of ‘Longa Vida’ and ‘Italiano’ tomatoes submitted to ultrasound treatment at 25 kHz for 0 (control), 15, and 30 min were evaluated. The results showed that ultrasound did not compromise the physical and chemical characteristics of ‘Longa Vida’ and ‘Italiano’ tomatoes. Therefore, through the development of this thesis, it was possible to conclude that the tomatoes were safe for human consumption and that the application of ultrasound at different times does not interfere with the quality of ‘Longa Vida’ and ‘Italiano’ tomatoes. Nevertheless, further research on the effect of ultrasound on pesticide residues must be carried out.